ESTIMASI KEBUTUHAN DAYA LISTRIK DI SULAWESI SELATAN SAMPAI TAHUN 2025 - Wildan Wildan (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2019)
This study aims to determine the amount of electric power needs each year in South Sulawesi until 2025. This estimation aims to determine the large power needs of South Sulawesi until 2025 by using the DKL 3.02 method used to estimate the need for electric power in the future based on data the use of energy and electric power, population growth, and economic growth in South Sulawesi Province, namely the GDP of South Sulawesi Province from previous years before the estimated year. The estimated results of the total electricity demand for all sectors from 2015 amounted to 2,452,130,065 VA and up to the year 2025 amounted to 5,246,811,618 VA with an average growth of 7.48%.